The risk of cardiac failure following metal-on-metal hip arthroplasty. (January 2018) - Sabah, S. A.; Moon, J. C.; Jenkins-Jones, S.; Morgan, C. Ll.; Currie, C. J.; Wilkinson, J. M.; Porter, M.; Captur, G.; Henckel, J.; Chaturvedi, N.; Kay, P.; Skinner, J. A.; et al.
Abstract : Aims: The aim of this study was to determine whether patients with metal-on-metal (MoM) arthroplasties of the hip have an increased risk of cardiac failure compared with those with alternative types of arthroplasties (non-MoM). Patients and Methods: A linkage study between the National Joint Registry, Hospital Episodes Statistics and records of the Office for National Statistics on deaths was undertaken. Patients who underwent elective total hip arthroplasty between January 2003 and December 2014 with no past history of cardiac failure were included and stratified as having either a MoM (n = 53 529) or a non-MoM (n = 482 247) arthroplasty. The primary outcome measure was the time to an admission to hospital for cardiac failure or death. Analysis was carried out using data from all patients and from those matched by propensity score. Results: The risk of cardiac failure was lower in the MoM cohort compared with the non-MoM cohort (adjusted hazard ratio (aHR) 0.901; 95% confidence interval (CI) 0.853 to 0.953). The risk of cardiac failure was similar following matching (aHR 0.909; 95% CI 0.838 to 0.987) and the findings were consistent in subgroup analysis. Conclusion: The risk of cardiac failure following total hip arthroplasty was not increased in those in whom MoM implants were used, compared with those in whom other types of prostheses were used, in the first seven years after surgery. Cite this article: Bone Joint J 2018;100-B:20–7.